THE ROLE OF THE THEMATIC APPROACH IN IMPROVING THE QUALITY OF LEARNING IN ELEMENTARY SCHOOLS - Mifta Sri Lastari (Teaching and General Education Studies, 2026)
The thematic approach is a learning strategy that combines various subjects into one particular theme so that the learning process becomes more complete and meaningful. Through this approach, students do not study the material separately but rather connect various concepts from subjects such as science, social studies, Indonesian, mathematics, and art into one unit. This article discusses the basic concepts, implementation, benefits, and obstacles in using the thematic approach in elementary schools. The results of the study show that this approach is able to improve students' understanding of the material, foster learning motivation, develop creativity, and strengthen social skills. However, there are still several challenges, such as limited learning resources and teachers' abilities in managing thematic learning. With good planning, use of appropriate learning media, and improvement of teacher competency through training, these obstacles can be overcome. Therefore, a thematic approach can be a solution to improve the quality of learning to be more interesting, relevant, and in accordance with students' daily lives.